Paediatric cerebral vasculopathy in sickle cell anaemia: contribution of genetic modifiers - Silva, Marisa (2019)
Sickle cell anaemia (SCA) arises from homozygosity for the mutation c.20A>T in the HBB gene. However, it shows a multifactorial-like behaviour with high heterogeneity of clinical features. Cerebral vasculopathy (CVA), namely paediatric ischemic stroke, is one of its most devastating consequences. The risk of CVA development, specifically stroke or silent cerebral infarction, may be modulated by underlying genetic modifiers, for example those affecting vascular homeostasis. In this study, we aimed to investigate the impact of variants in genes related with endothelial adhesion (VCAM1 and ITGA4) and nitric oxide metabolism (NOS3) on CVA in a group of 70 SCA children well characterized according to their CVA degree. In addition, the effect of the same genetic variants on biochemical/haematological biomarkers of chronic haemolysis was also analysed. Moreover, we also evaluated the putative additional modulating role of variants previously identified as stroke risk factors by genome-wide associated studies: GOLGB1 Y1212C, ENPP1 K173Q and PON1 Q192R. Molecular analysis was performed using PCR, PCR-RFLP, next-generation sequencing and Sanger sequencing. SPSS software was used for statistical analyses and association studies. One of the seven VCAM1 promoter haplotypes found and the VCAM1 promoter rs1409419_T showed association with moderate to high time-averaged mean of maximum velocity in the middle cerebral artery. The same association was observed for the variant ENPP1 K173Q. On the other hand, we observed that ITGA4 variants rs113276800_A and rs3770138_T were associated with stroke events. As for NOS3, one of the six haplotypes and the intron 4 VNTR_4b allele (5 repeats) were associated with lower risk of silent cerebral infarction. Chronic haemolysis biomarker levels also seemed to be influenced by genetic variants. LDH levels was higher in the presence of VCAM1 promoter rs1409419_T and one VCAM1 haplotype but lower in patients with one of the two ITGA4 haplotypes found. Genetic modulation also occurred in total bilirubin levels, which were higher in association with VCAM1 rs3783613_C allele. Our results, namely the association between specific variants with certain cerebral vasculopathy predictors further enhances their putative modulating effect on SCA paediatric stroke risk, severity and prognosis. These findings provide additional clues on the SCA pathophysiology and uncover features in these genes that may prove to be crucial as potential therapeutic targets.